Conic sections in ferroelectric nematics: Experiments and mathematical modeling - Priyanka Kumari; Olexandr Kurochkin; Vassili G. Nazarenko; Oleg D. Lavrentovich; Dmitry Golovaty; Peter Sternberg (Physical Review Research)
The domain structure of a fluid ferroelectric nematic is dramatically different from the domain structure of solid ferroelectrics since it is not restricted by rectilinear crystallographic axes and planar surface facets. We demonstrate that thin films of a ferroelectric nematic seeded by colloidal inclusions produce domain walls (DWs) in the shape of conics such as a parabola. These conics reduce the bound charge within the domains and at the DWs. An adequate description of the domain structures requires one to analyze the electrostatic energy, which is a challenging task. Instead, we demonstrate that a good approximation to the experimentally observed polydomain textures is obtained when the divergence of spontaneous polarization—which causes the bound charge—is heavily penalized by assuming that the elastic constant of splay in the Oseen-Frank energy is much larger than those for twist and bend. The model takes advantage of the fact that the polarization vector is essentially parallel to the nematic director throughout the sample.